Global communication - Hamelink, Cees. (Thousand Oaks, CA : Sage Publications, 2014)
A student introduction to the history, present and future of global communication from one of Europe's most respected communication scholars.
What is Global Communication? How to Study Global Communication The History of Long-Distance Communication The Economy of Global Communication Flows of Global Content Emergence of the Politics of Global Communication The Politics of Global Communication: 21st Century Issues Inequality and the Global Divide Propaganda, Diplomacy and Espionage Global Communication and Global Conflict Culture and Global Communication Global Communication Online Futures of Global Communication
Includes bibliographical references and index.
Keywords: Communication, International